New Result of Analytic Functions Related to Hurwitz Zeta Function. (12th December 2013) - Ghanim, F.; Darus, M.
Abstract : By using a linear operator, we obtain some new results for a normalized analytic function f defined by means of the Hadamard product of Hurwitz zeta function. A class related to this function will be introduced and the properties will be discussed.